PEMAHAMAN GURU PAUD TERHADAP AKTIVITAS JASMANI BAGI ANAK PAUD SE-KECAMATAN MUARA BANGKAHULU - Oddie Barnanda Rizky; Muhammad Habibie; Andika Prabowo; Andes Permadi; Septian Raibowo (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2023)
This study aims to determine the understanding of PAUD teachers on physical activity for PAUD children in Muara Bangkahulu District. This study uses a qualitative method. The subjects in this study were 8 PAUD teachers in Muara Bangkahulu District. Instruments and data collection techniques used in this study were observation, interviews, and questionnaires. The results of the observational research obtained a value of 75% (medium), 25% (high), while the results of the questionnaire obtained a percentage value with an average of 56.11%. Based on the results of the study it can be seen that the level of understanding of PAUD teachers regarding physical activity for PAUD children in Muara Bangkahulu District is categorized as moderate because teachers already have an understanding of physical activity, but there are still teachers in teaching and learning that are not in accordance with predetermined learning programs. The importance of PAUD teacher understanding of physical activity to support children can move actively through their gross motor skills.